Versões de manejos de água nos documentos do Fórum Mundial da Água e do Fórum Alternativo Mundial da Água - Souza, Jonas Eduardo Tavares de (2019)
In the summer of 2014/2015, the Metropolitan Region of São Paulo (RMSP) experienced the greatest water supply crisis of its history. The main water supply system of the RMSP, Cantareira, which served 9 million people before the crisis, almost collapsed. After almost four years, the flow of water to the population during the drought period of 2018, from April to August, registered only almost 1/3 of the average for this period, and since that crisis, the Cantareira System began to serve only 5.6 million people. Why were the technical efforts, the high sums invested and a period of almost four years, not enough to solve this problem? In April 2018 the World Water Forum and the World Alternative Water Forum were held in Brasilia, events created to discuss and address local and global water related issues. Thousands of people from various areas participated as technicians of private and public companies, politicians, promoters, workers, indigenous peoples and traditional populations who manage water in different ways, directly or indirectly, and who have different conceptions of human relations with water , to the point where the two forums occur simultaneously but separately, and there is no institutional and official dialogue between them. Annemarie Mol, a philosopher of Theory Network Actor (TAR), has developed the concept of multiple versions of objects that can coexist in the real world and be regimented by power relations that make one version stand out, necessarily. The objective of this research is to know the versions and the proposals for the water management that circulated in these forums. For this, discursive analyzes of two public domain documents were carried out, one from each forum, to find the terms associated with water management and the flow of ideas that compose the documents. Three versions of water management were found: water as an element of nature, water with economic value and water as a public good. Three empirical examples have been described to illustrate these versions: that of Rio Vilcabamba in Ecuador, as a subject of rights; the conflict over water in the province of Petorca in Chile as an economic good and the Payment for Ecosystem Services (PES) in the municipality of Extrema, Brazil, as a public good. As a conclusion we have in common in the three cases the discursive practices through legal-legal processes as responsible for the institutionalization of these versions of water management, and in addition, different versions of water between forums, as an element of nature, as a value economic and as a public good, which hinder dialogue between them